Stress analysis of various shaped PMMA using Babinet compensator in reflection polariscope - Yongyut Manjit (2020)
© 2020, Chiang Mai University. All rights reserved. The induced stress relations of PMMA (Poly methyl methacrylate) were investigated by two-point loading of hydraulic press system at top and bottom 535.4, 688.6, 841.6 and 994.6 N of various shapes in square, octagon, dodecagon and circular disk. All of samples had the same diagonal length and thickness of 2.5 and 0.6 cm respectively. We observed the number of fringe order of isochromatic fringe pattern at first quadrant of sample by using Babinet compensator in reflection polariscope. The net number of fringe order was used to calculate the relative maximum number of fringe order in horizontal direction of sample by equation of Nmax-Ni. And this parameter was used to analyze the stress distribution in samples. It was found that the dark band could be observed at the edge of first straight edge of square, octagon and dodecagon shape but dark band did not appear on the edge of disk. The maximum fringe orders of octagon, dodecagon and circular disk at X/R = 0.0, Y/R = 0.9 were 15 fringe orders and the maximum fringe order of square at X/R = 0.0, Y/R = 0.8 was 8.81 fringe orders. Fringe order at contact area decreased along vertical direction and minimum fringe orders at X/R = 0.5, Y/R = 0.0 of square, octagon, dodecagon and circular disk were 3.53, 3.35, 2.62 and 3.72 fringe orders respectively. The relative number of fringe order of square was more than octagon and dodecagon. It means that the transmission of stress in horizontal direction of square was more than octagon and dodecagon.